About criteria of an estimation of steady development of region - V. A. Svetlosanov; V. N. Kudin; A. N. Kulikov (Юг России: экология, развитие)
The problem of regional sustainable development is considered. The number of population for integral description (criterion) of regional sustainable development is accepted. The method of construction of the mathematical regional model for Kirovsk-Apatity region is suggested. The conclusion on regional unsustainable development beginning on 1990 year till now is done. The scenario of regional development to the condition of sustainable development is model demonstrated.